2021
DOI: 10.21203/rs.3.rs-1009107/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabarcoding Reveals High Diversity of Benthic Foraminifera Driven by Atlantification of Coastal Svalbard

Abstract: Arctic marine biodiversity is undergoing rapid changes due to global warming and modifications of oceanic water masses circulation. These changes have been demonstrated in the case of mega- and macrofauna, but much less is known about their impact on the biodiversity of smaller size organisms, such as foraminifera that represents a main component of meiofauna in the Arctic. Several studies analysed the distribution and diversity of Arctic foraminifera. However, all these studies are based exclusively on the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
(122 reference statements)
1
0
0
Order By: Relevance
“…Monothalamids were more common in sediment samples. Previous studies based on 18S rRNA metabarcoding showed that sediment samples routinely contain a high number of monothalamids that can often not be reliably assigned to a lower taxonomic level ( Rodrigues et al, 2021 ; Nguyen et al, 2021 ), which is in line with our results. We speculate that more small, amoeboid monothalamid taxa were lost during sieving and decantation of the meiofauna fraction, and that they were therefore present in higher abundance in the sediment samples.…”
Section: Discussionsupporting
confidence: 92%
“…Monothalamids were more common in sediment samples. Previous studies based on 18S rRNA metabarcoding showed that sediment samples routinely contain a high number of monothalamids that can often not be reliably assigned to a lower taxonomic level ( Rodrigues et al, 2021 ; Nguyen et al, 2021 ), which is in line with our results. We speculate that more small, amoeboid monothalamid taxa were lost during sieving and decantation of the meiofauna fraction, and that they were therefore present in higher abundance in the sediment samples.…”
Section: Discussionsupporting
confidence: 92%